The B corp certification in Germany: an analysis of factors influencing the decertification of B corps - Hufen, Marie (2022)
This paper explores factors provoking certified B Corps to reconsider their certification status in Germany and thus, bridges a research gap on decertification. To investigate this issue, the author follows a qualitative research design that relies on ten semi-structured interviews with company representatives, who provide insights on critical factors and potential pitfalls. Although B Corp certification presents a promising tool, the German B movement is found to be at risk due to its lack of benefits, mainstream transformation, underestimation of renewal and internal stakeholder changes. The implications of the findings are discussed by means of propositions and recommendations for further research. On this basis, B Lab can take timely action and strengthen its vision of “using business as a force for good.”